A governança metropolitana da mobilidade: Uma análise a partir dos Estados - Vicente Correia Lima Neto; Rômulo Dante Orrico Filho (Instituto de Pesquisa Econômica Aplicada (IPEA), 2015)
– The public transportation is known as a public service of common interest and it is the constitutional basis for the formulation of metropolitan areas by the states governments. This article develops a critical analysis from fourteen Brazilian metropolitan regions reports of the Metropolitan Governance project. The appraisal is based on four factors: the legality of the service, the use of public consortium as a governance arrangement, the presence of mobility plans at metropolitan or municipal level and the distribution of funds from the Brazilian's Growth Acceleration Program. The cases shows evidence of possible solutions. The best cases of the metropolitan transport management processes are related with a more present state in the metropolitan transportation planning, helping with the structuring planning tools and coordinating the process of cohesion of the municipalities.
Keywords: O18; H76; H77; R48; R52; 330; mobility; metropolitan region; metropolitan governance